Musical experience influences socio-emotional functioning in behavioural variant frontotemporal dementia - van’t Hooft, Jochum J.; Benhamou, Elia; Albero Herreros, Claudia; Jiang, Jessica; Levett, Benjamin; Core, Lucy B.; Requena-Komuro, Mai-Carmen; Hardy, Chris J. D.; Tijms, Betty M.; Pijnenburg, Yolande A. L.; Warren, Jason D. (Frontiers in Neurology, 2024)
Objectives On phenotypic and neuroanatomical grounds, music exposure might potentially affect the clinical expression of behavioural variant frontotemporal dementia (bvFTD). However, this has not been clarified. Methods 14 consecutive patients with bvFTD fulfilling consensus diagnostic criteria were recruited via a specialist cognitive clinic. Earlier life musical experience, current musical listening habits and general socio-emotional behaviours were scored using a bespoke semi-quantitative musical survey and standardised functional scales, completed with the assistance of patients’ primary caregivers. Associations of musical scores with behavioural scales were assessed using a linear regression model adjusted for age, sex, educational attainment and level of executive and general cognitive impairment. Results Greater earlier life musical experience was associated with significantly lower Cambridge Behavioural Inventory (Revised) scores (β ± SE = −17.2 ± 5.2; p = 0.01) and higher Modified Interpersonal Reactivity Index (MIRI) perspective-taking scores (β ± SE = 2.8 ± 1.1; p = 0.03), after adjusting for general cognitive ability. Number of hours each week currently spent listening to music was associated with higher MIRI empathic concern (β ± SE = 0.7 ± 0.21; p = 0.015) and MIRI total scores (β ± SE = 1.1 ± 0.34; p = 0.014). Discussion Musical experience in earlier life and potentially ongoing regular music listening may ameliorate socio-emotional functioning in bvFTD. Future work in larger cohorts is required to substantiate the robustness of this association, establish its mechanism and evaluate its clinical potential.